PEMAKSAAN MENIKAH OLEH ORANG TUA ANGKAT PERSPEKTIF MAZHAB SYAFI'I (STUDI PUTUSAN PA NO. 3298/PDT.G/2024/PA.SMDG) - Adnan Maulana; Deni Irawan (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to examine the practice of forced marriage by adoptive parents within the framework of Shafi'i jurisprudence, taking Decision No. 3298/Pdt.G/2024/PA.Smdg as a case study. It is a normative legal research employing a qualitative approach. The data were gathered through literature review, using primary legal materials in the form of court decisions, along with secondary legal sources derived from Shafi'i fiqh books and relevant statutory regulations. The findings reveal that the Shafi'i school recognizes the right of ijbar only for biological fathers and grandfathers, thereby excluding adoptive parents acting as guardians (kafalah) from holding such authority. In this case, the panel of judges annulled the marriage due to the absence of the bride’s consent, as stipulated in Article 6 of Law No. 1 of 1974 and Article 71 letter (f) of the Compilation of Islamic Law. This decision illustrates the alignment between positive law and sharia principles, particularly the maxim ad-dhararu yuzal (harm must be eliminated), to ensure the protection of individual rights in marriage.